2009
DOI: 10.1590/s0100-72032009000600008
|View full text |Cite
|
Sign up to set email alerts
|

Aloimunização

Abstract: Revisão ResumoAloimunização é a formação de anticorpos quando há a exposição do indivíduo a antígenos não próprios, como ocorre, por exemplo, na transfusão de sangue incompatível e nas gestantes, cujos fetos expressam em suas células sanguíneas antígenos exclusivamente de origem paterna. Este artigo se restringe à aloimunização contra antígenos eritrocitários em pacientes obstétricas. Quase todos os anticorpos antieritrocitários podem ser enquadrados em um dos 29 sistemas de grupos sanguíneos já reconhecidos, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 54 publications
0
5
0
8
Order By: Relevance
“…It is one of most common inherited single gene disorder [9,10]. Different ß thalassemia carrier screening programmes are being conducted throughout the world, as this is the only effective way of reducing the incidence of thalassemia major births [11][12][13][14]. In Pakistan ß thalassemia has a carrier rate of 5%.…”
Section: Discussionmentioning
confidence: 99%
“…It is one of most common inherited single gene disorder [9,10]. Different ß thalassemia carrier screening programmes are being conducted throughout the world, as this is the only effective way of reducing the incidence of thalassemia major births [11][12][13][14]. In Pakistan ß thalassemia has a carrier rate of 5%.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, immature fetuses are subjected to intrauterine transfusion therapy to treat moderate or severe anemia and avoid the development of such conditions as hydrops and intrauterine death. 11 Illanes & Soothill 12 further argue that antenatal therapies can modify but are not able to fully revert the hemolytic process, determining that surveillance and neonatal care are necessary measures for an adequate outcome during follow-up. When studying the early outcome of infants subjected to intrauterine transfusion therapy, McGlone et al, 13 observed that exchange transfusion was necessary in 20% of newborns.…”
Section: Discussionmentioning
confidence: 99%
“…More severe fetuses that underwent intrauterine transfusion therapy had scheduled cesarean section deliveries, which increased the rate of complications related to prematurity, such as hyaline membrane syndrome. 11 Currently, the trend in the management of these fetuses is to keep them in a serial intrauterine transfusion therapy treatment plan up to the 35th week, with a delivery planned for three weeks later. This management plan has had good results with respect to neonatal outcome and had even reduced the need for exchange transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Two publications, one from Tunis and one from Brazil [15,16], reinforced the importance of Rh Immune Globulin in pregnant D‐negative women, use of Doppler ultrasound studies of the fetal middle cerebral artery and use of intrauterine transfusion.…”
Section: Alloimmunization and Management In Pregnancymentioning
confidence: 99%